Management of complications associated with percutaneous left atrial appendage closure with or without ablation: experience from 512 cases over a 4-year period - Zou, Qi; Jiang, Cheng; Lin, Pengyang; Yu, Yangyang; Li, Jiazheng; Zhao, Feng; Hu, Hao; Sun, Shougang (Frontiers in Cardiovascular Medicine, 2024)
Background Percutaneous left atrial appendage closure (LAAC) serves as an alternative prophylactic strategy for patients with non-valvular atrial fibrillation (AF) who cannot undergo anti-coagulation therapy. Proper management of associated complications is crucial to enhancing the procedure's success rate and mitigating perioperative risks and adverse events during follow-up. Aims This study aims to summarize our center's experience and strategies in managing procedural-related complications encountered in 512 cases of LAAC with or without ablation for AF conducted from January 2020 to December 2023. Results We identified 11 significant intervention-requiring complications associated with LAAC with or without Ablation procedure. These included three cases of intraoperative thrombosis, three instances of pericardial effusion or tamponade, one case of device-related thrombosis, one peri-device leak, one systemic embolism, one bleeding episode, and one additional device-related complication. The categorization of intraoperative thrombosis was as follows: one patient exhibited heparin resistance; one experienced thrombosis due to prolonged device implantation during the LAAC with ablation procedure; and one had unexplained intraoperative thrombosis. The pericardial effusion or tamponade likely resulted from damage to the atrial appendage during LAAC device insertion. Two patients encountered device-related thrombosis and systemic embolism events possibly caused by non-standard postoperative antithrombotic medication use; one patient's peri-device leak may have resulted from incomplete endothelialization of the occluder post-surgery; one patient experienced postoperative bladder bleeding; and one patient's device-related complications occurred due to a dislodged strut frame that damaged the left atrial appendage, leading to pericardial effusion. Our proactive interventions enabled all patients with these surgical-related complications to be safely discharged, with subsequent follow-ups showing no adverse events. Conclusion Implementing targeted interventions for immediate procedural-related complications during the LAAC with or without ablation procedures enhances procedural success rates, diminishes postoperative mortality and patient disability, and bolsters stroke prevention efforts. This approach underscores the importance of a strategic response to complications, affirming the procedure's viability and safety in managing non-valvular AF in patients contraindicated for anticoagulation.